ONLINE FOOD BUSINESS: IS IT EATING UP OVERALL SALES OR GROWING IT (WITH SPECIAL REFERENCE TO ZOMATO AND SWIGGY) - Mr. Rahul Sharma, Dr Chandra Prakash Gupta, Mr. Jitendra Dubey (International Journal of Advanced Science and Technology, 2020)
India is becoming digital. Name any sector and you will find number of sites selling the related products or services online. Flipkart and Amzon have taken the Indian digital market place by storm. Another interesting emergence is of the launch of Swiggy and Zomato in Indian digital landscape for delivering any type of food, any time and from any type of food outlet of the city. You move out on the roads any time in a day and you will find Swiggy and Zomato guys standing outside number of fast food joints, restaurants and confectioner ready to deliver the food orders to the hungry. Giants like Pizza Hut, Dominos, and many other reputed restaurants across the country have started taking orders online, via phones, sites or mobile apps also in there city of operation. This online revolution in the food market has changed the way food business is being done hence making it an interesting area for study. What is actually happening at the food market place because of this online revolution? Food business on rise, stationary or going down is to be explored. Researcher decided to study the impact of online delivery systems developed by Swiggy and Zomato on the sales of the food outlets.